The Mediating Role of Consumer Trust between Influencer Credibility and Emotional Brand Attachment among Skintific Consumers in Yogyakarta, Indonesia - Puspita Anggraeni Prabowo; Nina Fapari Arif (Golden Ratio of Mapping Idea and Literature Format, 2026)
The beauty industry in Indonesia is experiencing significant growth, particularly in the skincare sector. Influencer marketing strategies are key to building emotional relationships with consumers. This study aims to analyze the effect of influencer credibility on emotional brand attachment, with consumer trust as a mediating variable among Skintific users in Yogyakarta. Using quantitative methods and a survey of 139 Generation Z respondents, data were analyzed with PLS-SEM in SmartPLS 4. The results show that influencer credibility has a significant positive effect on consumer trust and emotional brand attachment. Consumer trust partially mediates this relationship, indicating that influencer credibility will be more effective in building emotional brand attachment when it first fosters trust. These findings confirm that influencer credibility serves as the initial foundation for the psychological mechanism of trust, which, in turn, creates long-term emotional brand attachment. The limitations of this study lie in the limited geographic scope of Yogyakarta. Therefore, future research is recommended to expand the population reach to a national scale, adopt a longitudinal approach, and consider variables such as perceived authenticity and consumer engagement to yield more comprehensive results.